L'article 4 du Statut de Westminster et la souveraineté du Canada - Sormany, Louis (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1979)
The object of this paper is to inquire whether s. 4 of the Statute of Westminster, considered as an ordinary statutory provision, really constitutes a legally binding assurance that the Parliament of the United Kingdom may not pass laws for Canada without the latter's consent. In its first part, the paper discusses the validity of such an Act intended for application in Canada, that would not contain the declaration contemplated in s. 4. This is examined in reference to the principle of Parliamentary sovereignty and to the question as to the capacity of Parliament to bind itself for the future. The conclusion reached is that, because Canadian courts could treat s. 4 as an entrenched clause binding upon the United Kingdom Parliament, such an Act could be ruled invalid. The paper then discusses the case of a United Kingdom Act containing a declaration that Canada has requested and consented to such legislation, while in fact Canadian initiative or acquiescence would be lacking. The conclusion there is that s. 4, whether considered in isolation or together with the Preamble to the Statute, would not warrant a ruling of invalidity by Canadian courts. In particular, allegations of error or fraud in the passing of the Act would not make it invalid. The general conclusion is therefore that s. 4 does not really constitute a legally binding assurance that the United Kingdom Parliament may not pass laws for Canada without the latter's consent. While the legal issue discussed in this paper may seem academic, since the British Parliament was never, since 1931, attempted to pass laws intended for application in Canada without the latter's consent, it throws an interesting light on the foundations of Canadian sovereignty. The paper suggests that such sovereignty seems to be based at least as much on constitutional convention than on s. 4 of the Statute of Westminster.